REKRUTMEN POLITIK DAN KOMUNIKASI POLITIK PARTAI GERINDRA DALAM KANDIDASI WALIKOTA BANDUNG 2024-2029 - Sabarudin, Didin (UKRI, 2024)
Abstract Indonesia is facing simultaneous national regional head elections in 2024 to elect Governors, Regents, and Mayors in 38 provinces and 514 districts and cities. Political parties have a central position in regional head elections through political recruitment to take part in electoral competitions at all levels in accordance with the mandate given by laws and regulations regarding political parties, general elections, and regional head elections. The recruitment of the Gerindra party for the candidate for Mayor/Deputy Mayor of Bandung is recommended to Prabowo Subianto's trusted young figure, R. Dhani Wirianata number 07-1051/REKOM/DPP-GERINDRA/2024 dated 18 July 2024 which was signed by the General Chairperson and Secretary General after going through selection with open and closed methods. Dhani's figure is believed to be able to accelerate development and solve the problems of the city of Bandung as the political communication of the Gerindra party in the form of political messages and public opinion is conveyed through the candidacy declaration of R. Dhani Wirianata carrying the tagline